PUBLIC SECTOR EFFICIENCY IN INDONESIA (FISCAL DECENTRALIZATION ERA, 2001 â2008 - Kirana, Mayanggita; Saleh, Samsubar (Journal of Indonesian Economy and Business, 2011)
While many developing countries have devolved public responsibilities to local governments in recent years, some studies have examined whether decentralizationactually leads to greater public sector allocation efficiency. This paper approaches this question by assessing the efficiency of government expenditure on public sector underfiscal decentralization. The area of public expenditure is of great importance making the findings have strong implications with regard to public sector efficiency.We compute public sector performance (PSP) and public sector efficiency (PSE) indicators, comprising of composite and 9 sub indicators, for 33 provinces in Indonesia.The first 6 sub indicators are opportunity indicators that take into account education, health outcomes, poverty, gender equality, quality of public infrastructure (transportationand energy). 3 order indicators reflect the standard musgravian tasks for the government: allocation, distribution, and stabilization. The input and output efficiency of public sectors across provinces is then measured using a non-parametric production frontier technique.Free Disposable Hull (FDH) analysis is used to estimate the extent of slack in government expenditures. The study finds significant differences in PSP and PSE, which suggests alarge potential for expenditure savings in many provinces. All these findings suggest diminishing marginal products of higher public spending.We also estimate a semi parametric model of the public sector production process by regressing FDH analysis output scores on non discretionary variables using the Tobit procedure. We show that inefficiency is strongly related to GDP per capita, human development index, and degree of fiscal dependence. The central message of this paper is that increasing budgetary allocations for public sector may not be the only or most effective way to increase public sector outcome, and that more attention should be given to increasing the efficiency of expenditure.Keywords: fiscal decentralization public sector performance, public sector efficiency, free disposable hull, Tobit